Pengembangan Sistem Informasi Point of Sales Rumah Makan berbasis Web (Studi Kasus: Rumah Makan Pindang Ombai Kota Prabumulih) - Nadir Ruayuanda Bakri; Satrio Agung Wicaksono; Djoko Pramono (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
Pindang Ombai Restaurant is one of the restaurants located in Prabumulih City. This restaurant has several problems, including has no reservation activity, the cashier is still manual without a machine, and long income calculation. This study uses four initial stages in the waterfall method, namely the stages of requirements analysis, system design, system implementation, and system testing. Requirements analysis stage will produce 2 as-is business processes, 3 to-be business processes, 12 identification features to be made, 19 functional requirements, and 18 use cases and use case scenarios. System design stage will produce 10 sequence diagrams, 2 class diagrams, 1 relational data model, and 13 user interfaces. System implementation stage uses the PHP programming language with the Laravel framework and uses MySQL as the DBMS which produces 7 controllers and 4 models. System testing stage uses validation testing which is a black box test and produces 100% valid results for 29 test cases, which means the system has met the specified requirements. In addition to validation testing, user acceptance testing was also carried out and resulted in 93.78% which means strongly agree that the system can be accepted by users.